Composite binder as well as preparation method and application thereof

By using composite adhesives composed of polyethylene oxide, polyvinylpyrrolidone, polyaniline and water-soluble lithium silicate, the existing lithium-ion battery positive electrode material adhesives in terms of thermal stability, mechanical strength and electrochemical properties are solved. Inadequately, higher lithium-ion battery performance and lower costs are achieved.

CN119161835APending Publication Date: 2024-12-20新疆理工学院
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411287224.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The binder of the existing lithium-ion battery positive electrode material has shortcomings in improving battery performance, safety and environmental protection, especially in terms of thermal stability, mechanical strength and electrochemical performance, and the cost is relatively high. .

Method used

Using a composite binder, a CB binder composed of polyethylene oxide (PEO), polyvinylpyrrolidone (PVP), polyaniline (PANI) and water-soluble lithium silicate, is adopted to obtain specific compositional proportions and preparation methods. It forms a composite adhesive with good thermal stability, electrolyte wetting and bonding properties, and is used in the positive electrode of lithium-ion batteries.

Benefits of technology

It improves the thermal stability, cycle stability and electrochemical properties of lithium-ion batteries, reduces the volume expansion effect of active substances, enhances the bonding strength and conductivity, extends the cycle life of the battery, and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005043437790000021
    Figure BDA0005043437790000021
  • Figure BDA0005043437790000022
    Figure BDA0005043437790000022
  • Figure BDA0005043437790000031
    Figure BDA0005043437790000031
Patent Text Reader

Abstract

The invention discloses a composite binder as well as a preparation method and application thereof, and relates to the field of lithium ion battery positive electrode materials. The composite binder is composed of polyoxyethylene (PEO), polyvinylpyrrolidone (PVP), polyaniline (PANI) and lithium silicate, and is called a CB binder for short. According to the invention, the optimal ratio of the components is determined through a simple and convenient physical blending process, so that the binder with high viscosity and excellent electrochemical performance is obtained. In addition, the binder can also effectively reduce the volume expansion of the active substance in the charging and discharging process, and the overall performance of the battery is further improved. The preparation process is simple and efficient, and the obtained composite binder not only has excellent electrochemical performance, but also has huge market application potential, and is expected to make an important contribution to the progress of a lithium ion battery technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lithium ion battery positive electrode materials, and specifically relates to a composite binder and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries are widely used in today's life, and their importance is growing. These batteries are mainly used in industries such as electronic equipment, electric vehicles, and energy storage devices. Due to the strong demand for new energy vehicles, the market demand for lithium-ion batteries, as their core components, is growing rapidly. With the continuous advancement of technology, the market requirements for lithium-ion batteries are getting higher and higher, mainly focusing on improving energy and power density, extending cycle life, enhancing safety and environmental protection, and promoting the research and development and application of new materials. These requirements are aimed at meeting the growing market demand, especially in the field of electric vehicles and mobile electronic devices.

[0003] In lithium batteries, although the binder only accounts for a small part of the electrode system (4%-10%), the choice of binder has a direct impact on the performance of lithium-ion batteries. The binder can tightly adsorb the active material and the conductive agent on the current collector to prevent the active material from falling off the current collector, thereby building a complete and firm conductive network; the binder can evenly disperse the active material and the conductive agent to form a network with good electron and ion permeability, and achieve efficient conduction of electrons and lithium ions. The ideal binder should have good electrochemical stability, mechanical properties and compatibility with electrode materials. With the continuous development of lithium-ion battery technology, the requirements for binders are also constantly increasing, including higher thermal stability, better electrochemical performance and higher mechanical strength.

[0004] In the positive electrode of lithium-ion batteries, the use of composite binders can improve the overall performance of the battery, including electrochemical performance, mechanical performance, safety and environmental friendliness, compared with the single binder of traditional polyvinylidene fluoride (PVDF), and also help reduce costs. With the continuous development of lithium-ion battery technology, the requirements for binders are also increasing, so composite binders have become an important research direction.

[0005] Therefore, preparing a composite binder with good lithium ion conduction efficiency, good electrochemical properties, mechanical properties, safety and environmental friendliness is the trend and requirement of future market development. Summary of the invention

[0006] The purpose of the present invention is to provide a composite binder and a preparation method and application thereof. The composite binder is used to help improve the comprehensive performance of lithium-ion batteries, including the thermal stability and cycle stability of lithium-ion batteries, and can also improve the energy density and power density of the battery to a certain extent, which is of great significance for promoting the application of battery technology in new energy vehicles and energy storage fields.

[0007] The technical solution adopted by the present invention is as follows:

[0008] A composite binder is composed of polyethylene oxide (PEO), polyvinyl pyrrolidone (PVP), polyaniline (PANI) and water-soluble lithium silicate. The obtained composite binder is called CB binder.

[0009] Polyethylene oxide, also known as polyethylene glycol (PEG) when its molecular weight is less than 20,000 g / mol, is a common polymer compound composed of many ethylene glycol units connected by ether bonds and has a linear structure. Its structural formula is:

[0010]

[0011] Polyvinylpyrrolidone, referred to as PVP, is a polymer of vinylpyrrolidone. Due to its different degree of polymerization, it is divided into soluble PVP and insoluble PVPP. Soluble polyvinylpyrrolidone (such as PVP-K90) is not only soluble in common solvents such as water, methanol, ethanol, N-methylpyrrolidone (NMP), dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), but can also be used as a matrix to dissolve in other molten matrices, such as polyethylene glycol (PEG), to make a composite matrix, and its structural formula is:

[0012]

[0013] Polyaniline (PANI) is a polymer compound with special electrical and optical properties. It can have electrical conductivity and electrochemical properties after doping. The molecular chain of polyaniline contains alternating single bonds and double bonds, that is, conjugated structure. In this structure, carbon atoms are arranged in sp 3 Or sp hybrid orbital bonding. The localization of p orbital is relatively weak, p electrons cannot be fixed in a specific area, and there is a tendency to delocalize, and electrons can jump to conduct electricity. Polyaniline (PANI) can form a graft copolymer with polyvinyl pyrrolidone (PVP), and the resulting product is a PVP molecular main chain dragging a polyaniline molecular side chain with a certain length dissolved in the reaction medium. Among them, the eigenstate structure of polyaniline is:

[0014]

[0015] Furthermore, in the CB binder, the composition of each substance is: 8 to 12 parts by mass of polyethylene oxide, 48 to 52 parts by mass of polyvinyl pyrrolidone, 18 to 22 parts by mass of polyaniline, and 18 to 22 parts by mass of lithium silicate; preferably, 8 to 10 parts by mass of polyethylene oxide, 49 to 51 parts by mass of polyvinyl pyrrolidone, 19 to 21 parts by mass of polyaniline, and 20 to 22 parts by mass of lithium silicate; more preferably, 8 to 9 parts by mass of polyethylene oxide, 50 to 51 parts by mass of polyvinyl pyrrolidone, 20 to 21 parts by mass of polyaniline, and 21 to 22 parts by mass of lithium silicate.

[0016] The preparation method of the above CB binder comprises the following steps:

[0017] S1. PEO, PVP and PANI were dissolved in NMP according to the above mass fractions and stirred to obtain a PEO-PVP-PANI mixed solution;

[0018] S2. The above mass fraction of lithium silicate was dissolved in distilled water and stirred to obtain a lithium silicate solution;

[0019] S3. Blend the two mixed solutions obtained from S1 and S2 to obtain CB binder slurry.

[0020] The above-mentioned binder is applied to the positive electrode of a lithium-ion battery, and specifically comprises the following steps:

[0021] First, a positive electrode active material (such as lithium iron phosphate) and a conductive agent (such as acetylene black) are added to the above-obtained CB binder slurry to obtain a uniform viscous slurry; then the above-mentioned viscous slurry is coated on an aluminum foil and dried to obtain a positive electrode sheet.

[0022] The beneficial effects of the present invention are:

[0023] (1) The CB binder obtained by the present invention has good thermal stability, electrolyte wettability and ionic conductivity;

[0024] (2) The CB adhesive obtained by the present invention has good bonding performance and bonding strength;

[0025] (3) The CB binder obtained by the present invention can reduce the volume expansion effect of the active material. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 These are SEM images of LiFePO4 positive electrodes prepared with different binders in Example 1 and Comparative Example 1, wherein a, b, and c are SEM images of PVDF / LiFePO4 electrodes, and d, e, and f are SEM images of CB / LiFePO4 electrodes.

[0027] Figure 2This is a comparison chart of the room temperature rate performance test of LiFePO4 batteries prepared with different binders in Example 1 and Comparative Example 1, where (a) corresponds to a temperature of 25°C and (b) corresponds to a temperature of 50°C.

[0028] Figure 3 The figure is a comparison chart of the room temperature cycle performance and charge and discharge curves of LiFePO4 batteries prepared with different binders in Example 1 and Comparative Example 1.

[0029] Figure 4 This is a comparison of the AC impedance spectra of LiFePO4 batteries prepared with different binders in Example 1 and Comparative Example 1 before and after cycling.

[0030] Figure 5 This is a comparison of the cyclic voltammetry curves of LiFePO4 batteries prepared with different binders in Example 1 and Comparative Example 1 before charge and discharge. DETAILED DESCRIPTION

[0031] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments, but the present invention is not limited thereto.

[0032] Example 1

[0033] A CB adhesive is prepared from the following components by weight: 0.008 g of polyethylene oxide, 0.050 g of polyvinyl pyrrolidone, 0.020 g of polyaniline, and 0.022 g of lithium silicate.

[0034] The preparation method of the above CB binder comprises the following steps:

[0035] a. Weigh 0.008 g PEO, 0.050 g PVP-K90 and 0.020 g PANI in a weighing bottle, add an appropriate amount of NMP and stir to obtain a PEO-PVP-PANI mixed solution;

[0036] b. Weigh 0.022 g of lithium silicate and dissolve it in distilled water and stir to obtain a lithium silicate solution;

[0037] c. Blending the two mixed solutions to obtain composite CB binder slurry.

[0038] The above-mentioned CB binder is applied to the positive electrode of a lithium-ion battery, and specifically comprises the following steps:

[0039] (1) LiFePO4, acetylene black, and CB binder were weighed in a mass ratio of 8:1:1 (the mass of CB binder was calculated based on the total mass of all components);

[0040] (2) adding LiFePO4 and acetylene black to the CB binder slurry in sequence to obtain a uniform viscous slurry;

[0041] (3) The slurry was coated on aluminum foil and vacuum dried at 80° C. for 24 h to obtain a LiFePO4 positive electrode sheet. The specific proportions of the components of the above substances are shown in Table 1.

[0042] Table 1

[0043] name PEO PVP-K90 PANI Lithium silicate <![CDATA[LiFePO4]]> Acetylene Black Weight(g) 0.008 0.050 0.020 0.022 0.800 0.100

[0044] Among them, the sum of the masses of PEO, PVP-K90, PANI and lithium silicate is 0.1 g, which is the same as the mass of acetylene black;

[0045] The mass ratio of LiFePO4: acetylene black: composite binder is 8:1:1, and the total mass is 1.0 g.

[0046] Comparative Example 1

[0047] Preparation of positive electrode sheet containing control binder (polyvinylidene fluoride):

[0048] a. Weigh LiFePO4, acetylene black, and reference binder polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1 respectively;

[0049] b. LiFePO4 and acetylene black were added to the control binder slurry in sequence to obtain a uniform viscous slurry; c. The slurry was coated on an aluminum foil and vacuum dried at 80°C for 24 hours to obtain a LiFePO4 positive electrode sheet. The specific proportions of the components of the above substances are shown in Table 2.

[0050] Table 2

[0051] name <![CDATA[LiFePO4]]> Acetylene Black PVDF Weight(g) 0.800 0.100 0.100

[0052] Among them, PVDF binder is the most commonly used binder at present and is used as a control binder in the present invention.

[0053] Lithium-ion battery assembly:

[0054] The positive electrode sheet of LiFePO4 containing CB binder in Example 1 or the positive electrode sheet of LiFePO4 containing PVDF binder in Comparative Example 1 was punched into discs with a diameter of 14 mm and placed in a glove box filled with argon for later use. In the glove box, a CR2032 button half-cell was assembled using a lithium sheet as the negative electrode, LiFePO4 as the positive electrode, 1 mol·L-1 LiPF6-EC / DMC / EMC (1:1:1, mass ratio) as the electrolyte, and Celgard 2500 polypropylene porous membrane as the separator.

[0055] Depend on Figure 1It can be seen that when scanning and observing at 1000 times, the surfaces of the two pole pieces are smooth and flat; from the SEM results of 10,000 times and 50,000 times, it can be seen that in the LiFePO4 positive pole piece prepared with PVDF binder, the positive electrode material and acetylene black are unevenly dispersed, and the LiFePO4 material particles are mostly exposed and not completely covered by the conductive agent; while in the LiFePO4 positive pole piece prepared with CB binder, the positive electrode material and acetylene black are relatively evenly dispersed, and only a few LiFePO4 material particles are exposed, which are relatively completely covered by the conductive agent, forming a conductive network.

[0056] Electrochemical performance test:

[0057] CB binder and PVDF binder were simultaneously applied to LiFePO4 positive electrode materials to prepare positive electrode sheets. After physical property tests such as flexibility and adhesion and scanning electron microscopy tests were performed on the sheets, they were assembled into button half-cells and electrochemical performance tests were performed under different conditions.

[0058] At room temperature (25+2℃), different rates (0.2C, 0.5C, 1C, 2C, 5C, 10C, 0.2C) performance tests were carried out, and 10 charge and discharge cycles were performed at each rate. The results of the room temperature rate performance test are as follows: Figure 2 shown.

[0059] from Figure 2 It can be seen that the LiFePO4 batteries prepared with different binders were tested for rate performance at room temperature. When the charge and discharge cycle was carried out at a low rate of 0.2C, the maximum discharge specific capacity of the lithium iron phosphate battery prepared by PVDF and the LiFePO4 battery prepared by CB conductive binder were 154.1mAh / g and 158.0mAh / g, respectively. The maximum discharge specific capacity of the LiFePO4 battery prepared by CB conductive binder increased by 2.5%. Moreover, the LiFePO4 battery prepared by PVDF binder showed continuous attenuation after reaching the maximum discharge specific capacity in the third cycle; the LiFePO4 battery prepared by CB binder only had a slight attenuation after reaching the maximum discharge specific capacity in the seventh cycle. When the charge and discharge cycle was carried out at high rates such as 0.5C, 1C, 2C, 5C, and 10C, the discharge specific capacity of the LiFePO4 batteries prepared by the two binders was not much different, but the discharge specific capacity of the LiFePO4 battery prepared by CB binder was still higher.

[0060] The performance of two groups of LiFePO4 batteries prepared with CB binder and PVDF binder was compared after 100 cycles of 0.5C charge and discharge at room temperature 25°C and the charge and discharge curves of the 50th cycle are shown in the figure below. Figure 3 As shown. Figure 3It can be seen that in the early stage of the charge and discharge cycle, the discharge specific capacity gradually increases, and as the number of charge and discharge times increases, the discharge specific capacity gradually reaches stability. After 100 cycles, the discharge specific capacity of the battery prepared with PVDF binder decays; the discharge specific capacity of the LiFePO4 battery prepared with CB binder does not decay. This shows that the LiFePO4 battery prepared with CB binder has better cycle stability. It can also be seen from the charge and discharge curves of the two groups of batteries in the 50th cycle that the CB binder reduces the charge and discharge polarization of the LiFePO4 battery, thereby improving the charge and discharge specific capacity.

[0061] Two groups of LiFePO4 batteries prepared with CB binder and PVDF binder were subjected to 100 charge and discharge cycles at 0.5C. AC impedance tests were performed before and after charge and discharge. The results are shown in Figure 2. Figure 4 As shown. Figure 4 It can be seen that the AC impedance graphs of LiFePO4 batteries prepared by CB binder and LiFePO4 batteries prepared by PVDF binder before and after cycling are the same. The AC impedance before cycling has only one semicircle, and the AC impedance after cycling has two semicircles. The resistance of LiFePO4 batteries prepared by CB binder before and after cycling is lower than that of LiFePO4 batteries prepared by PVDF binder. The charge transfer impedance of the two groups of batteries before cycling is 605.51Ω and 1002.80Ω respectively; the SEI internal resistance after cycling is 90.18Ω and 202.89Ω respectively, and the charge transfer impedance is 235.92Ω and 490.08Ω respectively. The results show that the resistance of LiFePO4 batteries prepared by CB binder is reduced, which may be because the positive electrode material and the conductive agent are more evenly distributed in the positive electrode sheet of LiFePO4 prepared by CB binder, and the positive electrode material is completely covered by the conductive agent, forming a better conductive path and reducing the internal resistance of the electrode.

[0062] The electrochemical performance of two groups of LiFePO4 batteries prepared with PVDF binder and CB binder was further analyzed. Cyclic voltammetry scanning test was performed before charge and discharge test. The scanning times were 2 times. The cyclic voltammetry test results are shown in Figure 2. Figure 5 As shown. Figure 5 It can be seen that the cyclic voltammetry curves of the LiFePO4 battery prepared with CB binder are of the same shape, and the two cyclic voltammetry curves of different batteries are almost overlapped, indicating that the two groups of LiFePO4 batteries prepared with different binders have good cyclic reversibility. In the first cycle of the cyclic voltammetry curve, the LiFePO4 battery prepared with PVDF binder has an oxidation peak at 3.71V. At this time, Li + From the LiFePO4 structure; a reduction peak appears at 3.24V, at this time, Li +Embedded in the LiFePO4 structure, the potential difference between the two peaks is 0.47 V. In the first cycle cyclic voltammetry curve of the LiFePO4 battery prepared with CB binder, the oxidation peak and reduction peak are at 3.69 V and 3.23 V, respectively, with a potential difference of 0.46 V. From the potential difference, it can be seen that the LiFePO4 battery prepared with CB binder has a smaller potential difference and a larger current peak value corresponding to its oxidation peak, indicating that the battery prepared with CB binder has smaller charge and discharge polarization and smaller internal resistance.

[0063] In summary, the CB binder described in the present invention is used for positive electrode slurry, has good thermal stability, electrolyte wettability and ionic conductivity, can not only improve the cycle stability of lithium-ion batteries, but also can play a certain role in improving the battery specific capacity at different charge and discharge rates. Compared with PVDF binder, it shows good bonding performance and bonding strength, and reduces the volume expansion effect of active substances.

Claims

1. A composite adhesive, It is characterized in that The composite binder is composed of polyethylene oxide, polyvinyl pyrrolidone, polyaniline and water-soluble lithium silicate, and is called CB binder.

2. The composite adhesive according to claim 1, It is characterized in that The polyethylene oxide is formed by connecting ethylene glycol units through ether bonds and has a linear structure, and its structural formula is:

3. The composite adhesive according to claim 1, It is characterized in that The polyvinyl pyrrolidone is referred to as PVP, and its structural formula is:

4. The composite adhesive according to claim 1, It is characterized in that The polyaniline is referred to as PANI, and its eigenstate structural formula is:

5. The composite adhesive according to claim 1, It is characterized in that The composition of each substance in the CB binder is: 8 to 12 parts by mass of polyethylene oxide, 48 to 52 parts by mass of polyvinyl pyrrolidone, 18 to 22 parts by mass of polyaniline, and 18 to 22 parts by mass of lithium silicate.

6. The composite adhesive according to claim 1, It is characterized in that The composition of each substance in the CB binder is: 8 to 10 parts by mass of polyethylene oxide, 49 to 51 parts by mass of polyvinyl pyrrolidone, 19 to 21 parts by mass of polyaniline, and 20 to 22 parts by mass of lithium silicate.

7. The composite adhesive according to claim 1, It is characterized in that The composition of each substance in the CB binder is: 8-9 parts by mass of polyethylene oxide, 50-51 parts by mass of polyvinyl pyrrolidone, 20-21 parts by mass of polyaniline, and 21-22 parts by mass of lithium silicate.

8. A method for preparing the composite adhesive according to any one of claims 1 to 7, It is characterized in that The steps include: S1. PEO, PVP and PANI were dissolved in NMP and stirred to obtain a PEO-PVP-PANI mixed solution; S2. The lithium silicate is dissolved in distilled water and stirred to obtain a lithium silicate solution, wherein the mass parts of PEO, PVP, PANI and lithium silicate meet any one of claims 5 to 7; S3. Blend the two mixed solutions obtained from S1 and S2 to obtain CB binder slurry.

9. Use of the composite binder according to any one of claims 1 to 7 in a positive electrode of a lithium ion battery.

10. The use according to claim 9, It is characterized in that The application comprises the following steps: First, a positive electrode active material and a conductive agent are added to the slurry of the CB binder as claimed in any one of claims 1 to 7 to obtain a uniform viscous slurry; then the viscous slurry is coated on an aluminum foil and dried to obtain a positive electrode sheet.